PENGARUH KERJASAMA ORANGTUA DENGAN GURU TERHADAP PEMBENTUKAN AKHLAK SISWA SMPN 1 BONTOLEMPANGAN KECAMATAN BONTOLEMPANGAN KABUPATEN GOWA - Nursyabilah, Ifah; Bakri, Muhammad Ali; St. Muthahharah (Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this study is to find out the pattern of cooperation between parents and teachers, to find out the process of forming student morals, and to find out whether there is an influence from this collaboration. The research method used is a quantitative research method. Sources of data in this research are teachers and students. The research instrument used is a questionnaire or questionnaire. Data analysis technique using simple linear regression analysis. The sampling technique in this study was to use the Slovin formula with a confidence score of 20%. The results of the study can be summarized as follows: 1) There are 4 collaborations that researchers encounter in the field. 2) The process of forming the morals of students at SMP Negeri 1 Bontolemngan is classified as good as the average score for the variable of student moral formation has the highest score of 3.7 and the lowest score of 3,0. The percentage level was 141 or 64% with the number of categories that answered very often, 55 or 25% answered often, 29 or 13% answered rarely, and 7 or 3% answered not at all. 3) There is an influence of the cooperation of parents and teachers (X) on the formation of student morals (Y) at Bontolemngan 1 Public Middle School. The results of the influence can be seen from the t-table value of 2.085, meaning that the t-count value is (8.187) > t-table (2.085), then Ho is rejected and Ha is accepted, meaning that there is a significant influence found between parent-teacher cooperation on the moral formation of students at SMP Negeri 1 Bontolemangan. And the coefficient of determination in this study shows that the contribution of the independent variable of cooperation between parents and teachers (X) on the dependent variable on student moral formation (Y) at SMP Negeri 1 Bontolemngan is 22%, while the rest is influenced by other variables not analyzed in this study.